Key technologies for directional well drilling in high-pressure anhydrite salt layers - Zhen Nie; Zhenyou Zhang; Huihong Luo; Ke Zou (Natural Gas Industry B, 2018)
The Jeribe–Kirkuk reservoir is one of the major pay zones in the Halfaya Oilfield, Iraq, and its overlying 500 m thick Lower Fars anhydrite salt layer with a formation pressure coefficient of 2.25 acts as the caprock sealing. That's just why the first Jeribe–Kirkuk directional well experienced multiple drill pipe stickings and two side trackings, and the first horizontal well had to be completed with casing ahead of the schedule. Obviously, the drilling in the Lower Fars high-pressure anhydrite salt layer is faced with severe challenges. In this paper, the Lower Fars anhydrite salt layer was analyzed from the aspects of mechanical property, pore pressure, ground stress and rock mineral characteristics. Then, a mathematical model and criterion rules were established for borehole stability and wellbore deformation in the Lower Fars formations with different lithologies and the wellbore deformation in the process of well drilling was simulated. Finally, the high-density saturated salt water drilling fluid was specially developed for directional drilling in anhydrite salt layers, and the well trajectory and drilling program of directional wells were optimized. The following results were obtained. First, the most unstable zone in the Lower Fars anhydrite salt layer is composed of mudstones. As to the main reason for drill pipe sticking, the increase of rheological property after mudstone hydration leads to tight holes, so the neighboring anhydrites and salt rocks are pulled to collapse, which ultimately results in drill pipe sticking. Second, borehole deformation and instability in the Lower Fars layer intensify with the increase of inclination angle and wellbore opening time, and the risk of borehole instability increases sharply with the increase of wellbore opening time. Third, polyamine inhibitor BZ-HIB and polymer thinner JNJ are selected to optimize the formula of the high-density saturated salt drilling fluid, thus making its inhibition and rheology during the drilling in anhydrite salt layer improved effectively. Fourth, the kick off point of the Jeribe–Kirkuk directional well is moved upward to Upper Fars from Lower Fars. Specifically, the buildup section is in Upper Fars, the angle holding section is in Lower Fars, and the inclination angle and directional section length in Lower Fars are decreased, so the risk of drill pipe sticking is reduced. So far, it has been practically applied to 22 wells, showing that the drilling complexities in Ø311.2 mm hole have been effectively controlled. In 2016, the average drilling cycle was 35.8 days, 52.8% shorter than that in 2015, and the average ROP was increased by 122% from 3.3 m/h to 7.33 m/h. In conclusion, technological optimization has achieved good application results. Keywords: Halfaya oilfield, Iraq, High-pressure anhydrite salt layer, Wellbore deformation, Drill pipe sticking, Directional drilling, High-density saturated salt drilling fluid, Well trajectory